The United States’ Military-Industrial Complex and War Case Study: Afghanistan - Yousfi, Adnane; Mihoubi, Ahmed (University of Ammar Theledji -Laghouat, 2020)
Since the 1960s, the term "military-industrial complex" has been a quite controversial topic, especially in Western civilization, leading many experts in the field to attempt theorizing the term. This study aims at showing the function of the military-industrial complex, illustrating how harmful it is, and demonstrating its double standards, and therefore, its effects on the United States in particular and on the world. This study also aims at showing the military industrial complex’s developmental history and specifically how it functioned in Afghanistan to exploit the war to its advantage. To accomplish that, relevant data specific to the military industrial complex are collected, explored, and analyzed. The study found that the military industrial complex is, to a large extent, powerful, harmful, and corrupt. The military-industrial complex, especially in the United States, influences politics, economy, and society; therefore, it should be put into questioning